2006
DOI: 10.1103/physrevc.73.034612
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent aspects of the semiclassical approach in the analysis of heavy ion reactions

Abstract: The semiclassical approach is one of the fundamental tools used to investigate and analyze heavy ion reaction processes. We show in this contribution that the evolution of the motion that emerges from the knowledge of the semiclassical amplitudes for the reaction channels as a function of time cannot be taken as a reliable representation for an actual wave function of the intrinsic states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We could, in principle, choose for the illustrations the same system as in Refs. [11,13]. Such choice would certainly ease the comparison of the new results with figures that already appeared in these earlier works.…”
Section: Applicationsmentioning
confidence: 73%
See 4 more Smart Citations
“…We could, in principle, choose for the illustrations the same system as in Refs. [11,13]. Such choice would certainly ease the comparison of the new results with figures that already appeared in these earlier works.…”
Section: Applicationsmentioning
confidence: 73%
“…The scheme of Ref. [11] benefits from a previous work [13] where it was shown that a classical approach, complemented by well-tested quantification rules, can indeed reproduce those results with remarkable precision.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations